'Commodification of everything' arguments in the social sciences: Variants, specification, evaluation, critique. (May 2023) - Hall, Derek
Claims about 'the commodification of everything' are a staple of 21st century left (and some liberal) analysis and critique. These claims, however, are asserted much more often than they are backed up, and little attention has been devoted to thinking through how they might be substantiated or to what 'the commodification of everything' actually means. This paper contributes to contemporary debates over capitalism, commodification and politics by suggesting ways that commodification-of-everything arguments can be better specified and evaluated. It identifies four variants of commodification-of-everything claims; reviews and critiques the literature's uses of the terms 'commodity', 'everything' and 'thing'; and articulates three possible definitions of 'the commodification of everything' that raise additional questions about defining 'sale' and 'market' and the implications of thinking of things as commodities. The conclusion suggests reframings of the relationship between capitalism and commodification that seek to preserve the force of commodification-of-everything claims while avoiding their pitfalls.